Indoor smart farming by inducing artificial climate for high value-added crops in optimal duration - ur Rehman, Attique; Razzaq, Abdul; Altaf, Adnan; Qadri, Salman; Hussain, Aamir; Khan, Ali Nawaz; Rehman, Tausif -ur-; Sarfraz, Zaid (International Journal of Agricultural and Biological Engineering, 2023)
The global population is increasing rapidly as compared to food production; approximately three times more food would be required in 2050. Climate change affects crop production by causing sudden changes in weather conditions, including rain, storms, heat waves, doughiness, and water shortages. Farming with smart technology provides a productive solution. Smart farming is a productive solution that provides a great resource of income and improves the countries’ economy by exporting consumable goods and preventing food security problems. Smart agriculture provides a combination of flexibility, remote access, and automation through the use of intelligent control technologies. Many countries are working towards smart and intelligent agriculture farming that analyzes crop, soil fertility, pests and weeds, and other problems caused by mismanagement and incompetence. However, smart agricultural farming is less widely adopted in agriculture as a result of high costs and little understanding of technology. In this study, An artificial climate control chamber (ACCC) was designed for cultivating plants by controlling the optimal parameters, especially the light spectrum. In ACCC, influential plant factors such as light, moisture, humidity, and fertilizer concentration have been controlled intelligently. Light spectrum was controlled by time periods in the previous system, while in the system proposed in this study, the light was controlled by image processing. In an artificial control chamber, the plant growth stages have been determined through image processing techniques. Datasets of image images have been used to organize specific intensities of the light spectrum. This intelligent system provides aid in the speed breeding procedure through variant spectrums of light and fertilizers combinations. In the research study, the yield and quality of intelligent farming are enhanced. Keywords: indoor smart farming, artificial climate, high value-added crops, optimal duration, light spectrum, image processing DOI: 10.25165/j.ijabe.20231603.6863 Citation: Rehman A, Razzaq A, Altaf A, Qadri S, Hussain A, Nawaz A, et al. Indoor smart farming by inducing artificial climate for high values crops in optimal duration. Int J Agric & Biol Eng, 2023; 16(3): 240–246.